Incorporating of TiO2 with oxygenated fuel and post-injection strategy in CRDI diesel engine equipped with EGR: A step towards lower NOX, PM and enhance soot oxidation reactivity - Mohammed A. Fayad; Thaar M. Aljuwaya; Thaqal M. Alhuzaymi; Hassan Sh Majdi; Abbas J. Sultan; Miqdam T. Chaichan; Tawfik Badawy; Mohammed Sobhi (Case Studies in Thermal Engineering, 2024)
A mixture of diesel, biodiesel (from algae), and butanol was mixed with nano-titanium dioxide at 50 and 100 parts per million in this study under post-injection (PI) strategy and two rates (10 % and 20 %) of exhaust gas recirculation (EGR). In the literature, few studies have investigated how PI strategies effect on engine emissions and combustion performance from mixture of B16M20 by butanol (16 %), microalgae biodiesel (15 %) and diesel with variable EGR rates. To gain a better understanding of the effects of EGR rates on diesel engines running with B16M20 mixture, this study was conducted. The final fuel type test used B16M20 treated with 50 ppm and 100 ppm of nano-TiO2. Fuel specific fuel consumption (BSFC) increased by 3 % for both diesel and B16M20 when EGR was used, but PI reversed this trend. Nanoparticles added to B16M20 blend significantly contributing in decreased BSFC to 6.47 %. 100 ppm nano-TiO2 added to 10 % of EGR, along with PI, can achieve the same or enhance better brake thermal efficiency (BTE) by 4.53 % than pure diesel. The lowest NOX levels by 26.48 % were achieved with 100 ppm nano-TO2 and B16M20 with 20 % EGR. Because of EGR's high heat capacity and dilution effect, higher EGR rates result in higher soot levels. As a result of the PI strategy, the soot levels emitted from B16M20 reduced by 28.57 % compared with diesel fuel. At PI strategy presence (W PI) and adding 100 ppm nano-TiO2 into the B16M20 blend resulted in the lowest PM concentrations by 59 % compared to the diesel and without PI (W/O PI). PM emissions were significantly reduced at temperatures below 600 °C from B16M20 blend combustion with delay injection, 10 % EGR, and 100 ppm nano-TiO2. Soot oxidation was minimized through EGR, and enhanced by nano-TiO2. Adding this 100 ppm of nanoparticles to diesel fuel produced more reactive soot than diesel fuel alone.